Edukasi Kualitas Air Bersih Bebas Kontaminasi Bakteri Coliform pada Masyarakat Jungsereh Garut - Sugiah Sugiah; Gina Nafsa Mutmaina; Mamay Mamay; Lia Ma’artiningsih; Astari Nurisani; Muhammad Hadi Sulhan; Meti Rizki Utari (Jurnal Pengabdian Bidang Kesehatan, 2024)
Indonesian people still use dug wells as a source of clean water. The dug well itself has bacteriological qualities that are easily contaminated. Coliform bacteria such as Escherichia coli can cause diseases, one of which is diarrhea. Jungsereh Garut Village is an area that uses a lot of water from dug wells for daily needs such as drinking water. The aim of this outreach is to determine the quality of clean water free of coliform bacteria contamination in the Jungsereh Garut community. The target of this counseling is the community of Jungsereh Village RT.02 Kec.Mekarsari Garut, totaling 30 people. This outreach activity is a form of increasing public awareness of the quality of clean water for drinking water that is free of coliform bacteria contamination. The method of implementing this extension activity is in the form of material presentation, discussion and question and answer and filling out a questionnaire regarding the level of understanding whether there are differences before and after the intervention.